THE ROLE OF TEACHERS SOFT SKILLS IN ENHANCING CLASSROOM EFFECTIVENESS: EVIDENCE FROM UNIVERSITY FACULTY IN PAKISTAN - NAZ, MISS; TAHIR, DR. TEHSEEN; ISHFAQ, DR. UMBREEN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study examined the influence of university teachers’ soft skills on classroom effectiveness in the higher education context of Khyber Pakhtunkhwa, Pakistan. Using a correlational survey design, data were collected from 385 students and 357 faculty members through mirrored questionnaires measuring five dimensions of soft skills—communication, empathy, leadership, problem-solving, and teamwork—and their relationship to classroom effectiveness. Reliability analysis confirmed strong internal consistency (α = .87–.92). Correlation results indicated that all five soft skills were positively associated with classroom effectiveness, with teamwork and leadership showing the strongest associations. Multiple regression analysis further revealed that teamwork (β = .313, p < .001) and leadership (β = .259, p < .001) were the most significant predictors, jointly accounting for over 80% of the variance in classroom effectiveness (R² = .81). These findings highlight the critical role of teachers’ interpersonal and collaborative abilities in fostering effective learning environments at the university level. The study contributes empirical evidence from a Pakistani context, emphasizing the need to integrate soft skills training into faculty development programs. Limitations and directions for future research, including qualitative exploration and cross-regional comparisons, are discussed.